Multiple primary neoplasia in a bitch - Hüdaverdi Erer; Metin Münir Kıran; Tevfik Tekeli (Eurasian Journal of Veterinary Sciences)
In this case multiple primary neoplasia was deseribe d. Mixed tumor and papillary adenocarsinoma of mammary gl and, intrahepatic cystic cholangiocellular adenoma, vaginal fibramatosis and nodular hyperplasia of spleen were detected in a 10 years old setter bitch. This case was the first report on multiple primary tumors in different organs of dogs in Turkey.